2021
DOI: 10.1007/s11845-020-02492-0
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of the functional reach test and the hand grip strength test in older adults using nursing home services

Abstract: Objective This study aimed to determine the absolute and relative test-retest reliability of the functional reach test (FRT) and the handgrip strength test (HGST) in older adults using nursing homes. Methods Participants (≥ 65 years old), living in nursing homes or using their day care services, were distributed into a group without cognitive impairment (GWCI, n = 43) and a group with mild cognitive impairment (GCI; n = 22). A 1-week test-retest was performed for the FRT and the HGST. Relative reliability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This test is non-invasive and can be easily performed with minimal equipment (1). Data also indicate that the isometric handgrip strength test is highly reliable (intraclass correlation coefficient ≥0.90) in various populations (1)(2)(3). Due to these advantages (i.e., high reliability, non-invasiveness, ease of use), this test is commonly utilized in research.…”
Section: Introductionmentioning
confidence: 96%
“…This test is non-invasive and can be easily performed with minimal equipment (1). Data also indicate that the isometric handgrip strength test is highly reliable (intraclass correlation coefficient ≥0.90) in various populations (1)(2)(3). Due to these advantages (i.e., high reliability, non-invasiveness, ease of use), this test is commonly utilized in research.…”
Section: Introductionmentioning
confidence: 96%
“…The TUG, OLS, and FRT all used the mean values measured in the 3 test trials and had high reliability. [ 18 , 19 ]…”
Section: Methodsmentioning
confidence: 99%
“…The TUG, OLS, and FRT all used the mean values measured in the 3 test trials and had high reliability. [18,19] Walking was evaluated using the 10-meter walk test (10MWT) and a gait analyzer. The 10MWT measures the time taken to walk 10 m, and in this study, the walking time of the middle 10 m was measured by walking a 20 m path to exclude the acceleration and deceleration sections of walking.…”
Section: Outcome Measurementioning
confidence: 99%
“…Additionally, the handgrip strength test will be used as an objective indicator of muscular strength. Handgrip strength is a valid indicator of vitality and physical function in older adults (Labott et al, 2019) and has demonstrated a high test–retest reliability in clinical settings (Ferreira et al, 2021). Participants will perform the test standing and will be asked to squeeze as strong as they can twice per hand.…”
Section: Methodsmentioning
confidence: 99%